Financial Crisis In Malaysia: Repercussions To The Banking System - Tiruvapillai, Rajakumar (2001)
This research project discusses the causes, consequences and implication of the Malaysian banking crisis with reference to the East Asian Crisis. The research finds that many possible factors can explain the causes of the crisis. In fact , it is difficult to assign weightage to each factor. The East Asian crisis was partly due to financial liberalization and fundamental weakness in the financial syatems of the Asian nations. The crisis was then triggered off by financial panics and spread throughout the region via the contagion effect.